2022
DOI: 10.1002/car.2751
|View full text |Cite
|
Sign up to set email alerts
|

Road‐testing child protection typologies: A case study in Lebanon

Abstract: Over the past three decades a small number of influential writers have bravely attempted to develop theoretical models for understanding and comparing the complex development of child protection systems across different countries. The foremost frameworks have compared the dynamics of child protection arrangements in high-income countries, with little attention being given to middle-and low-income countries and, more specifically, the MENA region. This paper presents Lebanon's child protection model and highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent research reported by El-Hoss and Brown (2022) in Lebanon demonstrates how Lebanon has multiple, devolved, systems, both statutory and religious, and each contain characteristics which are enshrined in legislation, but it is not appropriate to try and identify a single state lead system. They also argue that the Lebanese example challenges any assumption that progress simply involves moving towards an increasingly state-centred and regulated model.…”
Section: Future Research Prioritiesmentioning
confidence: 99%
“…Recent research reported by El-Hoss and Brown (2022) in Lebanon demonstrates how Lebanon has multiple, devolved, systems, both statutory and religious, and each contain characteristics which are enshrined in legislation, but it is not appropriate to try and identify a single state lead system. They also argue that the Lebanese example challenges any assumption that progress simply involves moving towards an increasingly state-centred and regulated model.…”
Section: Future Research Prioritiesmentioning
confidence: 99%